2020
DOI: 10.1126/sciadv.aaz8670
|View full text |Cite
|
Sign up to set email alerts
|

Paleomagnetic evidence for modern-like plate motion velocities at 3.2 Ga

Abstract: The mode and rates of tectonic processes and lithospheric growth during the Archean [4.0 to 2.5 billion years (Ga) ago] are subjects of considerable debate. Paleomagnetism may contribute to the discussion by quantifying past plate velocities. We report a paleomagnetic pole for the ~3180 million year (Ma) old Honeyeater Basalt of the East Pilbara Craton, Western Australia, supported by a positive fold test and micromagnetic imaging. Comparison of the 44°±15° Honeyeater Basalt paleolatitude with previously repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 92 publications
(79 reference statements)
0
23
0
Order By: Relevance
“…The oldest supercontinent is late Archean in age, and palaeomagnetic data from the Kaapvaal and Pilbara cratons for the interval 2780-2710 Ma and from the Superior, Kaapvaal and Kola-Karelia cratons for 2700-2440 Ma suggest significant relative movements (Cawood et al, 2018). Brenner et al (2020) concluded that their new palaeomagnetic pole data from 3.18 Ga basalt in the East Pilbara required an average latitudinal drift of >2.5 cm/year for the 170 Ma preceding 3.18 Ga, a velocity comparable with those of modern plates.…”
Section: Other Evidence For the Onset Of Plate Tectonicsmentioning
confidence: 97%
“…The oldest supercontinent is late Archean in age, and palaeomagnetic data from the Kaapvaal and Pilbara cratons for the interval 2780-2710 Ma and from the Superior, Kaapvaal and Kola-Karelia cratons for 2700-2440 Ma suggest significant relative movements (Cawood et al, 2018). Brenner et al (2020) concluded that their new palaeomagnetic pole data from 3.18 Ga basalt in the East Pilbara required an average latitudinal drift of >2.5 cm/year for the 170 Ma preceding 3.18 Ga, a velocity comparable with those of modern plates.…”
Section: Other Evidence For the Onset Of Plate Tectonicsmentioning
confidence: 97%
“…3.2–2.5 Ga onset of some form of subduction tectonics that was either episodic or continuous. This work includes isotopic (e.g., Naeraa et al., 2012), geochemical (e.g., M. Tang et al., 2016), petrological (e.g., Brown & Johnson, 2018), geological (e.g., Pease et al., 2008), geochronologic (e.g., Condie & Puetz, 2019), and paleomagnetic (Brenner et al., 2020) studies supporting the onset of plate tectonics during the Meso and/or Neoarchean, alongside numerical modeling explorations and reconstructions suggesting >3.2 Ga operation of hot stagnant‐lid tectonics (Johnson et al., 2017; Moore & Webb, 2013). As such, it can be argued that the scientific community now approaches a consensus concerning when plate tectonics initiated, which would allow a stronger focus on addressing how and why this process occurred.…”
Section: Introductionmentioning
confidence: 99%
“…A recent paleomagnetism study of the Honeyeater Basalt in the East Pilbara Craton suggests a modern plate motion velocity of ≥2.5 cm/year between ca. 3.4-3.2 Ga (Brenner et al, 2020). Conversely, plate subduction before ca.…”
Section: Start Of Plate Subduction and Production Of Granitic Crustmentioning
confidence: 99%